Experimental log hauling through a traditional caribou wintering area - Harold G. Cumming; Bruce T. Hyer (Rangifer, 1998)
A 3-year field experiment (fall 1990-spring 1993) showed that woodland caribou (Rangifer tarandus caribou) altered their dispersion when logs were hauled through their traditional wintering area. Unlike observations in control years 1 and 3, radio-collared caribou that had returned to the study area before the road was plowed on January 6 of the experimental year 2, moved away 8-60 km after logging activities began. Seasonal migration to Lake Nipigon islands usually peaked in April, but by February 22 of year 2, 4 of the 6 had returned. The islands provide summer refuge from predation, but not when the lake is frozen. Tracks in snow showed that some caribou remained but changed locations. They used areas near the road preferentially in year 1, early year 2, and year 3, but moved away 2-5 km after the road was plowed in year 2. In a nearby undisturbed control area, no such changes occurred. Caribou and moose partitioned habitat on a small scale; tracks showed gray wolf (Canis lupus) remote from caribou but close to moose tracks. No predation on caribou was observed within the wintering area; 2 kills were found outside it. Due to the possibility of displacing caribou from winter refugia to places with higher predation risk, log hauling through important caribou winter habitat should be minimized.